The Use of English in Indonesian Adolescents Slang - I Dewa Putu Wijana (Journal of Language and Literature, 2014)
This paper aims at describing the use of English in Indonesian Adolescents slang broadly known as bahasa gaul, the colloquial variation that symbolizes intimate relationships among the youngsters. By using data extracted from three slang dictionaries, the investigation finds that most English expressions of various linguistic levels (word, phrase, and sentence) are formally and, or semantically changed to attain various communicative functions. Key words: slang, expression, and adolescent